Gallery 12: The Celestial Dome of El Sagrario de Quito - Ojeda, Almerindo E. (2014)
Unaided by optical instrumentation and guided solely by common sense, early watchers of the heavens concluded that the Earth stood at the center of a spherical universe, and that the Sun, the Moon, and the planets rotated about the Earth in perfectly circular orbits. The celestial bodies completing their revolutions about the Earth faster would be closer to it, while those taking longer would be farther away. Thus, the Moon would be the closest of the celestial bodies, followed, in turn, by Mercury, Venus, the Sun, Mars, Jupiter, and Saturn. The orbits of these luminaries defined seven nested spheres which were enclosed within an eighth—the sphere of the fixed stars, known also as The Firmament. It was furthermore believed that celestial bodies affected the course of events in all of the spheres nested within their orbits. Thus the Earth, being within the sublunar world , was affected, not just by the Moon, but by all the other celestial bodies as well.